Inclusión de tres niveles (2, 4 y 6%) de harina de plátano verde (Musa × paradisiaca) como fuente de carbohidratos en la alimentación de pollos broiler en el cantón Mejía. - Atty Rivera, Cristhian Patricio (2021)
This research work was carried out in Pichincha P0072ovince, Mejia Canton, El Chaupi Parish with geographical coordinates 0-35'27.5"S latitude and 78-39'33.1"W longitude, with an altitude of 3477 meters above sea level at an average temperature of 12 °C, 100 chickens of the Ross 308 line of one day of age were used in this investigation and it was continued until the 49th day (7 weeks) in order to evaluate the inclusion of three levels (2.4 and 6%) of green banana flour (Musa x paradisiacal) in the feeding of broiler chickens in Mejía canton. The birds were assigned to 4 dietary treatments; T0- (Witness Treatment-Base Diet), T1 (Base Diet + 2% of Inclusion of Green Banana Flour), T2 (Base Diet + 4% of Inclusion of Green Banana Flour) and T3 (Base Diet + 6% of Inclusion of Green Banana Flour). A completely random design (CRD) was applied with five repetitions in each treatment, presenting the homogeneous experimental units (CV: 6.18 %). The variance analysis was performed, with Duncan's significance tests at 5%, to show significant differences between treatments. The economic analysis was carried out by calculating the benefit / cost ratio (BCR). The best results were obtained by using the food diet with 6% of inclusion of banana flour (T3) with a higher weight gain, throughout the production cycle which ended with a weight gain of 561 gr, being the feeding of the chickens at all stages (start, growth and fattening) adequate, due to its high carbohydrate content; the highest consumption of food was obtained in the treatment T3 (3257.2 g) presenting a better conversion of the same treatment. With regard to channel quality it is concluded that the T3 treatment obtained a living weight of 3298 gr and a yield of 74.36% is obtained being the best treatment.